Acute effects of exercise posture on executive function in transient ischemic attack patients. (8th April 2017) - Faulkner, James; Stoner, Lee; Grigg, Rebecca; Fryer, Simon; Stone, Keeron; Lambrick, Danielle
Abstract: In patients with stroke or transient ischemic attacks (TIA), a decline in executive function may limit an individual's ability to process motor tasks and relearn motor skills. The purpose of this study was to assess the acute effect of exercise posture (seated vs. supine cycle ergometry) on executive function and prefrontal cortex perfusion in patients with TIA. Eleven TIA patients (65 ± 10 years) and 15 age‐matched, healthy controls (HC; 62 ± 7 years) completed two exercise tests to maximal capacity (one seated, one supine) and two 30‐min submaximal exercise tests (one seated, one supine). Executive function was assessed prior to and following (1.5 min post, 15 min post) the submaximal exercise tests using a Stroop task. Prefrontal cortex perfusion (total hemoglobin) was continuously recorded using near‐infrared spectroscopy. There was no Posture (seated, supine) × Group (TIA, HC) interaction for the Stroop task ( p  > .05). HC completed Stroop tasks significantly faster than TIA (51.9[ SD  = 10.3] vs. 64.2[8.5] s, respectively), while Stroop completion time significantly improved between baseline and 1.5 min post (61.3[10] vs. 58.1[9.4] s, respectively) and 1.5 min post and 15 min post (54.8[8.9] s). Posture and group had no significant influence on prefrontal cortex perfusion ( p  > .05). In summary, executive function improves to a similar extent in TIA and age‐matched, healthy controls following an acute bout of exercise, regardless of exercise posture. As acute improvements in executive function were maintained for 15 min, there could be an important window of opportunity for assigning executive tasks following exercise rehabilitation for patients with TIA.